The Fine Structure of the Adepidermal Reticulum in the Basal Membrane of the Skin of the Newt, Triturus - Salpeter, Miriam M. (The Rockefeller University Press, 1959)
The unique reticulum in the basal membrane of the adult newt's skin consists of a series of nodular swellings from which there radiate fibers. Electron micrographic studies showed that the nodules consist of layers of fibrillae arranged approximately and irregularly at right angles to one another. Some are packed to form a capsule; still others extend into the internodular zone to form the radiating fibers. The fibrils are banded and are revealed best after fixation with potassium permanganate. The reticulum is compared with that of the larval newt and the frog tadpole. The epidermal side of the reticulum is bounded by a membrane separated from the plasma wall of the epidermal cell by a clear space. These we have termed adepidermal membrane and space, and have compared them with similar structures in larvae.